Effects of Enzyme and Emulsifier on Process Cheese Quality - Lilik Eka Radiati (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2010)
The objective of this research was to find out the effect of rennin Mucor pusillus and emulsifier on cheese qualitity.  Optimalization of process cheese   was conducted by optimizing two factors enzyme (rennin calf and M. pusillus) and emulsifier (Trinatrium Citrate and Dinatrium hydrophosphate). The results showed that there were significant differences cheese quality (pH value, titratable acidity, water content, protein, fat, texture and sensory tests) between rennin calf and M pusillus enzyme process.  Adding Dinatrium Hidrophosphat shown the  highest sensory score  among the treatments.   Keywords: Cheese, enzyme, emulsifier